Indonesian tertiary EFL students’ problems in paraphrasing journal articles: a narrative inquiry - Qonita Irfayani; Chubbi Millatina Rokhuma (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
This study investigates the problems faced by EFL students and their coping strategies to deal with problems when paraphrasing journal articles. To achieve the study objectives, the researchers utilized a narrative inquiry design with two semi-structured interviews. The gathered data were then analyzed by using thematic analysis. Four EFL students participated in this study and shared their experiences regarding the problems they faced when paraphrasing journal articles. The findings presented that the four students perceived limited vocabulary, lack of awareness regarding the criteria for effective paraphrasing and the proper stages of paraphrasing, struggle to find the appropriate synonyms, and lack of grammar mastery. Furthermore, it was discovered that there were several strategies adopted by the students to overcome the problem of paraphrasing journal articles such as changing active to passive voice, eliminating unnecessary words, utilizing paraphrasing tools, and consulting with others. This research can be a form of self-reflection for the readers, especially students, to be more aware of the importance of mastering paraphrasing skills.